PENGARUH ORIENTASI PELANGGAN, KEPUASAN PELANGGAN YANG DIMEDIASI OLEH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN - Dodi Ria Atmaja; Rino Kurnia Afandi (JURNAL LENTERA BISNIS, 2024)
Competition in the service industry encourages companies to improve customer orientation and service quality in order to achieve customer satisfaction and loyalty. This study aims to analyse the relationship between customer orientation, service quality, customer satisfaction, and customer loyalty at Honda repair shops in Tangerang. Using a quantitative approach, this study involved 100 Honda repair shop customer respondents. Data was collected through an online questionnaire and analysed using Structural Equation Modeling (SEM). The results state that customer orientation has a positive effect with service quality and customer satisfaction, service quality affects customer satisfaction, service quality mediates the relationship between customer orientation and customer satisfaction, and customer satisfaction has a positive effect on customer loyalty. This research has a contribution to the Honda Workshop by making customer loyalty a final strategy of the Honda Workshop. It is recommended that Honda workshops improve customer orientation and service quality to increase customer satisfaction and loyalty. Research limitations include a relatively small sample size and limited geographic coverage, opening up opportunities for further research on a larger scale.